Serumanti-PLA2R antibody predicted treatment outcome in idiopathic membranous nephropathy - Zhang Xue-qin; Jiang Hong; Yang Shu-fen; Zhao Hong-juan; Lu Chen (Linchuang shenzangbing zazhi)
Objective To explore the predictive value of serum phospholipase A2 receptor antibody in determining the efficacy of rituximab in the treatment of idiopathic membranous nephropathy（IMN）.Methods From August 1,2017 to May 31,2020,a total of 120 IMN patients received rituximab for the first time or during long-term follow-ups were included.According to the serum level of phospholipase A2 receptor antibody, they were divided into the groups of positive and negative.The relevant data were compared between two groups.The remission rate of each group was analyzed by Kaplan Meier method and the remission rate between groups compared by log-rank test.Cox univariate and multivariate risk regression models were employed for adjusting the influencing factors of efficacy.Results Among 87 patients with positive serum phospholipase A2 receptor antibody, 9.1% and 6.9% achieved partial and complete remission versus 27.3% and 24.2% in serum phospholipase A2 receptor antibody negative group.The partial and complete remission rates after treatment with rituximab were higher in pla2 R-Ab positive group than those in negative group（χ2=5.057,P=0.0245;χ2=7.506,P=0.0061）.Conclusion The efficacy of rituximab is poor in the treatment of idiopathic membranous nephropathy with positive serum phospholipase A2 receptor antibody.Serum phospholipase A2 receptor antibody is an efficacy predictor of rituximab in IMN patients.